TRANSFORMASI PEMBUKUAN TRANSAKSI AKUNTANSI BAGI UMKM DENGAN APLIKASI BERBASIS SISTEM INFORMASI - Saraswati, Esti; Yuliarti, Lusi; Kristianto, Giovanny Bangun (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
MSMEs are currently one of the mushrooming businesses in Indonesia with increasingly rapid business development because it has increased National GRDP, so it is important for this development to be supported by increasingly complete financial aspects. In terms of financial recording, this is the main problem which is always a burdensome problem due to the lack of competence of MSME activists. Apart from financial problems, marketing activities are also another problem that is no less important. This problem is also faced by this community service partner, namely Aspikmas, South Purwokerto District. The use of digital technology is one solution that can alleviate MSME problems in the financial sector, because digital technology can make it easier to prepare financial reports easily, concisely and precisely. The existence of applications provided by the government, such as Lamriko, Siapik and Buku Warung, will overcome problems in terms of recording and bookkeeping. Complete and informative bookkeeping will be useful for banking capital needs, knowing financial performance both profit and loss and business strategies for MSMEs for the next period.